The Impact of School Closure on Adolescents' Wellbeing, and Steps towards to a New Normal: The Need for an Assessment Tool Update? - Leena Paakkari; Didier Jourdan; Jo Inchley; Minna Torppa (MDPI AG, 2021)
Close to 200 countries have implemented school closures to decrease the spread of the COVID-19 coronavirus. Though the closures have seemed necessary, their effects on the wellbeing of children and adolescents have raised serious concerns. To truly understand the impact of such disruption on young people's wellbeing, and their views on how to move towards a new normal, we must adopt different approaches to gather the data to secure children's and adolescents' rights to be heard in the issues that concern their lives. Current ways to examine the impacts of school closure have been dominated by gathering information concerning the children and adolescents, using mainly existing wellbeing indicators and related questionnaire surveys. Although such sources of information are important, they provide limited understanding of how children and adolescents have experienced school closures, especially if they have been produced using measures developed purely by adults. There is a need for information produced by children and adolescents themselves, which may require going beyond existing and pre-COVID theoretical wellbeing frameworks. By capturing information produced by children and adolescents, we can more effectively guide the development and evaluation of public health policies and identify solutions to mitigate the negative impacts of school closure, or to acknowledge the possible positive effects, and respond accordingly.